2014
DOI: 10.1103/physrevb.90.125431
|View full text |Cite
|
Sign up to set email alerts
|

Spin-flip Raman scattering of theΓXmixed exciton in indirect band gap (In,Al)As/AlAs quantum dots

Abstract: The band structure of type-I (In,Al)As/AlAs quantum dots with band gap energy exceeding 1.63 eV is indirect in momentum space, leading to long-lived exciton states with potential applications in quantum information. Optical access to these excitons is provided by mixing of the -and X-conduction-band valleys, for which their spins may be oriented by resonant spin-flip Raman scattering. This access is used to study the exciton spin-level structure by accurately measuring the anisotropic hole and isotropic electr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 34 publications
(47 reference statements)
1
19
0
6
Order By: Relevance
“…Note that for small values of ∆E ΓX an admixing of Γ and X-electron states takes place [8]. However, the effect of this admixing on the exciton fine structure is not in the focus of this paper.…”
Section: Optical Alignment and Optical Orientationmentioning
confidence: 92%
See 2 more Smart Citations
“…Note that for small values of ∆E ΓX an admixing of Γ and X-electron states takes place [8]. However, the effect of this admixing on the exciton fine structure is not in the focus of this paper.…”
Section: Optical Alignment and Optical Orientationmentioning
confidence: 92%
“…We will specify these QDs as the indirect QDs. It was shown that due to inhomogeneous broadening an ensemble of (In,Al)As/AlAs QDs is composed of direct and indirect dots, whose emissions are partly overlapping [6][7][8]10]. As we will show below, the direct and indirect QDs can be well distinguished from each other by different optical techniques.…”
Section: Energy Spectra Of Quantum Dotsmentioning
confidence: 99%
See 1 more Smart Citation
“…In low-dimensional structures the SFRS intensity is drastically increased by the presence of resident quantum-confined electrons that interact with photogenerated excitons. [21][22][23] In this paper we use the spin-flip Raman scattering technique to study the spin properties of CdSe colloidal nanoplatelets. By measuring ensembles of NPLs having various orientations in the Faraday and Voigt geometries of the external magnetic field and analyzing the polarization properties of the Raman spectra we determine the electron g-factor and its anisotropy.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the large band gap at the X point, the spin-orbit contribution to the electron g factor is vanishingly small [16,22]. As a result, the electron g factor, g e , is isotropic and its value almost coincides with the free-electron Landé factor of +2.0 [23]. The recombination times of the bright and dark excitons were unambiguously determined in Ref.…”
Section: A Parameters Used For Fittingmentioning
confidence: 99%